Do Market Prices Reflect Real Scarcity? Theories and Facts - Figueroa, Adolfo (Economia, 2019)
Do market relative prices reflect real scarcity of resources? If this were so, market prices would provide society with the correct signals about real scarcities. Economics—the science of scarcity— has different answers to this question. Following the principles of current epistemology, the paper reviews three theories of markets: neoclassical, bio-economics, and unified theory, analyzing their assumptions, their derived empirical predictions about the relation between market prices and scarcity, and their validity when confronted against known basic facts. Clarifying misconceptions about the nature and the role of the market mechanism in the functioning of capitalism is the expected contribution of the paper.